Columbo. Season four [videorecording (DVD)] - Falk, Peter, 1927-2011 (Universal classic television., 2012)
Everyone's favorite Police Lieutenant is back in his famous trench coat. Join Columbo as he asks all the right questions in some of the most deceptive and deadly cases. No murderer can hide for long with Columbo on the beat.